Determination of the environmental flow using a hydrobiological methodology, considering variables of climate change in the Pejibaye river, Cartago, Costa Rica - Watson-Hernández, Fernando (2021)
The environmental flow, in Costa Rica, is calculated as 10% of the average flow of the river. This percentage has lacked scientific basis in relation to the river conditions suitable for preserving the ecosystems present in the rivers. The water concessions for the different uses have caused an environmental impact that is reflected in the conditions of availability of the water resource in some vulnerable points of the country, as well as in the physicochemical and ecological conditions of the channels. The proposed project responds to the research route that seeks the selection and field validation of different methodologies to obtain the required environmental flow in a surface water source. In this particular case, the project is focused on the adaptation and validation of a hydrobiological methodology for calculating the environmental flow regime in Pejibaye river basin, Jiménez de Cartago. Historical hydrological data variables were used to analyze the current and projected future condition, the species of macroinvertebrates and fish that allowed evaluating the quality of the associated ecosystems were selected, finally, the hydraulic parameters of habitat preference were established to define the current environmental flow regime, whose results reveal a seasonality behavior, which is accentuated in the future projection. The insect genus Anacroneuria and the fish species G. nudus were determined to be the best for determining environmental flows.